Alterations along the Hypothalamic-Pituitary-Thyroid Axis of the Zebrafish (Danio rerio) after Exposure to Propylthiouracil. (9th August 2011) - Schmidt, Florian; Braunbeck, Thomas
Abstract : In the past, various approaches have been developed to detect adverse effects of pollutants on the thyroid of vertebrates, most of these with special emphasis on the South African clawed frog, Xenopus laevis . Although fish are primarily affected by thyroid-disrupting chemicals, studies into alterations of the thyroid of fish are scarce. Therefore, effects of the reference compound propylthiouracil on histopathology of the thyroid axis were analyzed in a modified early life-stage test with zebrafish ( Danio rerio ) exposed to propylthiouracil. The test substance induced dose-dependent alterations of thyroidal tissue concomitant with increases in the number of surrounding blood vessels. Despite this massive proliferation of the thyroid, zebrafish were not able to maintain thyroxin concentrations. The pituitary was affected displaying significant alterations in thyroid-stimulating hormone cell counts. Quantitative evaluation of pituitary surface areas revealed a dose-dependent increase of adenohypophyseal tissue. Distinct histopathological effects may contribute to a more easy identification and interpretation of alterations induced by thyroid-disrupting chemicals.